Analisis Praktek Bidan pada Pelayanan Ibu Bersalin dan Bayi Baru Lahir - Putra, Alhafiza (Kesmas, 2008)
Sekitar tigapuluh persen kematian bayi terjadi pada periode neonatal yang 80 % di antaranya terjadi pada minggu pertama. Hal tersebut mengindikasikan status kesehatan ibu dan bayi baru lahir yang rendah serta akses dan kualitas pelayanan persalinan masih rendah. Tahun 2006, kematian neonatal di Kabupaten Solo adalah 47 dari 8.250 kelahiran hidup dan di Kecamatan Lembah Gumanti adalah 23 kematian neonatal dari 1,091 kelahiran hidup. Tujuan penelitian ini untuk mengetahui pengaruh praktek bidan di wilayah kerja Puskesmas Alahan Panjang terhadap pelayanan ibu bersalin dan bayi baru lahir pasca persalinan. Penelitian dilakukan dengan metode kualitatif diskusi kelompok terarah, wawancara mendalam dan observasi. Informan adalah seluruh bidan yang bertugas di wilayah kerja Puskesmas Alahan Panjang, ibu bersalin yang persalinannya ditolong oleh informan bidan tersebut. Informan kunci adalah pimpinan dan koordinator program Kesehatan Ibu dan Anak (KIA) Puskesmas Alahan Panjang. Masih ada praktek yang tidak sesuai dengan Standar pelayanan kebidanan, terutama penyuluhan pada ibu bersalin. Supervisi yang dilakukan Pimpinan dan Koordinator Program KIA Puskesmas Alahan Panjang masih kurang. Bidan yang pernah mengikuti pelatihan fungsi bidan dalam pelayananan KIA sarana mendukung atau tindakan bidan dalam pelayanan KIA kurang. In Indonesia both Maternal and Infant Mortality Rates (MMR & IMR) has been significantly reduced. However, those figures were still higher than those of other ASEAN countries. About a third of infant deaths took place in the neonatal period, while 80% of the neonatal deaths happened during the first week of life. This was partly caused by both low accessibility and quality of care. The objective of this study was to assess the midwives’ practice during the provision of services in the post partum and early neonatal period. In addition, this study at Puskesmas Alahan Panjang was also aimed to identify supporting factors in delivering the above services. The design of this study was qualitative research design. The methods of data collection were focus group discussions (FGD), in-depth interview and observation. Results of the study showed that there were many practices of the midwives during postpartum and early neonatal period which did not follow the standard midwifery care by the Ministry of Health. Health education was not properly implemented and oftenly did not even take place. Supervision from the Puskesmas chief or midwife responsible for Maternal and Child Health (MCH) services was insufficient. There were very few midwives who ever joined training in improving their midwifery skills. It is urged that both District Health Office (Dinkes) of Solok and Puskesmas Alahan Panjang improve the competency of the midwives through appropriate training, supervision and provision of equipment and facilities. In addition, strengthening midwives in conducting effective health education program is also strongly recommended. In line with this effort, socialization of recent MCH programs and support for the development of “jorong” (Desa Siaga) is also of outmost importance.